Cycladic archaeology and research : new approaches and discoveries - Angliker, Erica; Tully, John (Archaeopress Publishing Ltd, 2018)
Recent excavations and new theoretical approaches are changing our view of the Cyclades. This volume aims to share these recent developments with a broader, international audience. Essays have been carefully selected as representing some of the most important recent work and include significant previously-unpublished material.